A construção e as artes ao tempo de D. Sesnando (Parte 1) - Fernandes, Paulo Almeida; Real, Manuel Luís (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2020)
D. Sesnando’s rule over a vast territory, between the rivers Mondego and Douro (1064-1091), entailed a rupture with the previous framework of territorial management, in which a considerable part of this land was nominally bound to Muslim authorities. After the definitive conquest of Coimbra, there was a period of intense change in the landscape and of enhancement of humanized geography, in which the alvazil Sesnando moved more intensely. This article seeks to address the reality of construction and the arts during D. Sesnando’s time, but it goes back to the beginning of the 11th century to highlight the great transformations that took place after 1064. Based on documental sources that mention various types of heritage, the first part of the paper offers an analysis of the territory. It also includes an introduction to the city of Coimbra, between the Muslim invasion of 711 and the eve of the 1064 conquest.